ナンキョク リュツオ・ホルム ワン チイキ ニ オケル カイヒョウ カンソク ニ ツイテ - 吉田, 栄夫; ヨシダ, ヨシオ; 森脇, 喜一; モリワキ, キイチ; Yoshida, Yoshio; Moriwaki, Kiichi (1990)
P(論文) 1981年, 南極リュツォ・ホルム湾内での海底地形調査を実施するに際して, 海氷調査が行われた。調査は, 地上および航空機による目視観測, NOAA衛星画像受信による海氷分布の推定, 昭和基地付近での経時的な海氷氷厚測定, および9月末から11月初めの一冬氷の厚さがほぼ最大になる時期の, 500kmの調査ルートに沿う氷厚測定などからなる。これらの調査は現時点で系統的な研究に結びつけることはできないが, 海氷研究のための基礎的な資料の蓄積に有用と考え, 結果を簡単に報告する。 We conducted the sea ice investigation in the Lutzow-Holm Bay region in 1981 in conjunction with the field work of submarine geomorphology. The investigation comprised observations on ground and from the air, simplified analysis of NOAA satellite images, and measurements of ice thickness in time sequence near Syowa Station and along 500-km long traverse routes during the period of the nearly maximum thickness of the first-year ice. The brief report presented here may be useful for future studies of sea ice conditions near Syowa Station. departmental bulletin paper